2013
DOI: 10.1002/dc.23013
|View full text |Cite
|
Sign up to set email alerts
|

Mycobacterial spindle cell pseudotumor: Atypical mycobacterial infection mimicking malignancy on fine needle aspiration

Abstract: A 58-year-old male operations manager with no significant past medical history presented with a 1.5 cm subcutaneous mass on the dorsal aspect of his left hand, between his thumb and index finger. While the mass had grown slowly over the prior six weeks, there was no associated pain, paresthesias, or weakness. The patient had no constitutional complaints or fever. He could recall no trauma or insect bites at the site and denied environmental exposures such as manicures or working with soil or standing water. He… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 7 publications
0
5
0
Order By: Relevance
“… reported a case of MSP of the nasal cavity in which nasal swabs for mycobacterial cultures were negative, but acid‐fast tissue stains yielded the correct diagnosis. Although acid‐fast staining of biopsy tissue in immunocompromised patients is clearly valuable, reports of MSP describe occasional cases involving non‐diagnostic acid‐fast staining in which the diagnosis required tissue culture or polymerase chain reaction‐based detection , or the inciting infection was ultimately identified as fungal rather than mycobacterial . In our case, acid‐fast staining and culture both implicated MAC as the causative agent.…”
Section: Discussionmentioning
confidence: 69%
See 1 more Smart Citation
“… reported a case of MSP of the nasal cavity in which nasal swabs for mycobacterial cultures were negative, but acid‐fast tissue stains yielded the correct diagnosis. Although acid‐fast staining of biopsy tissue in immunocompromised patients is clearly valuable, reports of MSP describe occasional cases involving non‐diagnostic acid‐fast staining in which the diagnosis required tissue culture or polymerase chain reaction‐based detection , or the inciting infection was ultimately identified as fungal rather than mycobacterial . In our case, acid‐fast staining and culture both implicated MAC as the causative agent.…”
Section: Discussionmentioning
confidence: 69%
“…In conclusion, the lack of infectious symptoms characteristic of MSP makes it difficult to differentiate clinically from malignancy and from other illnesses , such as lung cancer, Kaposi's sarcoma , inflammatory myofibroblastic pseudotumor, endemic fungal infection, or amiodaronoma . Recognition of this rare entity in the immunocompromised patient should foster persistence in obtaining tissue biopsy with tissue cultures and meticulous infectious work‐up of solitary pulmonary mass lesions in the solid organ transplant population.…”
Section: Discussionmentioning
confidence: 99%
“…Mycobacterial infections usually evoke an epithelioid (histiocytic) granulomatous reaction associated with Langhans giant cells and sometimes a neutrophilic infiltration and/or caseous necrosis. Within the soft tissue, atypical mycobacteria—most commonly M. avium-intracellulare complex—can induce the formation of mycobacterial spindle cell pseudotumors, which are composed of spindled histiocytes, scattered inflammatory cells, and rare MGCs 25–27. Leprosy, an infection caused by M. leprae that usually manifests with skin lesions, can also present with Langhans giant cells in association with epithelioid granulomata and caseous necrosis 28,29.…”
Section: Giant Cell-rich Tumors Of Soft Tissuementioning
confidence: 99%
“…Within the soft tissue, atypical mycobacteria-most commonly M. avium-intracellulare complex-can induce the formation of mycobacterial spindle cell pseudotumors, which are composed of spindled histiocytes, scattered inflammatory cells, and rare MGCs. [25][26][27] Leprosy, an infection caused by M. leprae that usually manifests with skin lesions, can also present with Langhans giant cells in association with epithelioid granulomata and caseous necrosis. 28,29 In a review of cutaneous mycobacterial infections giant cells were demonstrated in 60% of scrofuloderma (M. scrofulae) and 72.7% of lupus vulgaris (M. tuberculae).…”
Section: Mycobacterial Infectionmentioning
confidence: 99%
“…McGoldrick et al 2010 [10] 44M Lymph node (mediastinum) M. microti Steroid and azathioprine treated oral lichen planus Ilyas et al 2011 [45] 63M Nasal cavity MAC** Treated DLBCL☨ Yeh et al 2011 [9] 55M Skin M. chelonae Steroid treated scleroderma Alves et al 2012 [46] 28M Liver MTB*** AIDS Philip et al 2012 [7] 51F Lung MAI* AIDS Sideras et al 2013 [47] 42M Plantar fascia No culture HIV Ohara et al 2013 [6] 83M Nasal cavity MAI* HIV (Table 1 continued on page 37.) Rahmani et al 2013 [4] 79M Skin MAC** Solid organ transplant, Immunosuppressive therapy Holmes et al 2014 [48] 58M Skin M. chelonae None Ismail et al 2015 [49] 69M Brain MAI* Steroid treated sarcoidosis Franco et al 2015 [50] 69F Lung MAC** Solid organ transplant (lung), immunosuppressive therapy Lim et al 2016 [51] 66M Brain MAC** Steroid treated sarcoidosis Coelho et al 2017 [15] 13M Lymph node M. genavense Stem cell transplant, immunosuppressive therapy Thwaites et al 2018 [52] 88M Bone M. chelonae Diabetes Fonda-pascual et al 2018 [53] 50M Skin (penis) MAI* Combined immunodeficiency Dhibar et al 2018 [54] 38M Lymph node MTB*** AIDS Boylan et al 2018 [55] 33M Lung No culture AIDS Boylan et al 2018 [55] 45M Lung MAC** HIV Boylan et al 2018 [55] 69F Lung No culture None Taneja et al 2020 [56] 34M Lymph node MAC** AIDS Furlan et al 2020 [13] 42F Mycobacterial pseudotumors not only cause clinical and diagnostic confusion but can also confound the clinical picture as seen in the second case. This case showed hepatic diffuse large B-cell lymphoma as well as nodal MSP.…”
Section: Authorsmentioning
confidence: 99%